Tumor-targeting multifunctional micelles for imaging and chemotherapy of advanced bladder cancer. (August 2013) - Lin, Tzu-yin; Li, Yuan-Pei; Zhang, Hongyong; Luo, Juntao; Goodwin, Neal; Gao, Tingjuan; White, Ralph de Vere; Lam, Kit S; Pan, Chong-Xian
Aim: This work aimed to determine if the treatment outcomes of bladder cancer could be improved by targeting micelles that are decorated with bladder cancer-specific ligands on the surface and loaded with the chemotherapeutic drug paclitaxel.Materials & methods: Targeting efficacy and specificity was determined with cell lines. An in vivo targeting and anti-tumor efficacy study was conducted in mice carrying patient-derived xenografts.Results & discussion: Targeting micelles were more efficient than nontargeting micelles in delivering the drug load into bladder cancer cells both in vitro and in vivo (p < 0.05). The micelle formulation of paclitaxel was less toxic than free paclitaxel in Cremophor ® (Sigma, MO, USA) and allowed administration of three-times the maximum tolerated dose without increasing the toxicity. Targeting micelles were more effective than the nontargeting micelles in controlling cancer growth (p = 0.0002) and prolonging overall survival (p = 0.002).Conclusion: Targeting micelles loaded with paclitaxel offer strong potential for clinical applications in treating bladder cancer. Original submitted 16 March 2012; Revised submitted 30 August 2012; Published online 2 December 2012